Scale brightness of common goldfish on diet supplemented with seaweed Sargassum sp. and pumpkin Cucurbita moschata - Astari, Irfina Manda; Setyawati, Tri Rima; Yanti, Ari Hepi (Jurnal Akuakultur Indonesia, 2016)
ABSTRACT The common goldfish Carassius auratus auratus is an ornamental freshwater fish species with  high market value. The market value of ornamental fish can be determined through some parameters, one of them is brightness of the fish scales. Brightness level may be enhanced by supplementing plant powder containing carotenoid into fish diet. The purpose of this research was to examine the scale brightness level of common goldfish fed diet supplemented with Sargassum sp. and pumpkin powder, and to determine the dose of those powders that allows higher brightness level of scale.  The feed of common goldfish was supplemented with either Sargassum sp. or pumpkin powder at the doses of 10, 20 and 30%, and without supplementation as control. Fishes were reared for 75 days and fed diet at feeding rate of 5% biomass daily. The results of ANOVA test showed that the Sargassum sp. and pumpkin mill addition on food significantly improved of scales brightness of  common goldfish. Increasing supplementation levels of Sargassum sp. and pumpkin powder increased brightness level of scale. The highest improvement in brightness was the fish that fed by 30% concentration of Sargassum sp. flour with the value scale of brightness was 2.67 and the total number of 2,890.67 chromatophore cells. The results suggest that Sargassum sp. powder is better to improve the brightness level of common goldfish scale. Keywords: Carassius auratus auratus, Sargassum sp., Cucurbita moschata, carotenoid, brightness  ABSTRAK Ikan komet Carassius auratus auratus merupakan salah satu spesies ikan hias air tawar yang memiliki nilai jual tinggi. Nilai jual ikan hias dapat ditentukan melalui beberapa parameter, salah satunya yaitu kecerahan sisik ikan. Kecerahan sisik ikan dapat ditingkatkan melalui pemberian pakan yang diperkaya karotenoid. Tujuan penelitian ini adalah menguji tingkat kecerahan warna sisik ikan komet setelah diberi pakan dengan tambahan tepung Sargassum sp. dan labu kuning, dan menentukan dosis masing-masing tepung tersebut yang memberikan tingkat kecerahan tertinggi pada sisik ikan komet. Pakan ikan komet ditambahkan dengan tepung Sargassum sp. atau tepung labu kuning sebanyak 10, 20 dan 30%, serta tanpa suplementasi sebagai kontrol. Ikan dipelihara selama 75 hari dan diberi pakan uji sebanyak 5% biomassa setiap hari. Hasil uji ANOVA menunjukkan bahwa penambahan tepung Sargassum sp. dan labu kuning berpengaruh nyata terhadap peningkatan kecerahan sisik ikan komet. Semakin tinggi kadar tepung Sargassum sp. dan labu kuning yang ditambahkan ke pakan, maka semakin tinggi tingkat kecerahan sisik ikan komet. Tingkat kecerahan tertinggi terjadi pada ikan komet yang diberi pakan tambahan berupa tepung Sargassum sp. sebesar  30% dengan nilai kecerahan 2,67 dan jumlah kromatofor sebanyak 2.890,67 sel. Hal tersebut menunjukkan bahwa Sargassum sp. lebih bagus digunakan untuk meningkatkan kecerahan sisik ikan komet daripada labu kuning. Kata kunci: Carassius auratus auratus, Sargassum sp., Cucurbita moschata, karotenoid, kecerahan